2018
DOI: 10.1186/s10195-018-0510-2
|View full text |Cite
|
Sign up to set email alerts
|

How to prevent dislocation after revision total hip arthroplasty: a systematic review of the risk factors and a focus on treatment options

Abstract: BackgroundDislocation represents the most common complication after revision total hip arthroplasty (rTHA). Understanding risk factors for dislocation has a great clinical relevance for every hip surgeon in order to consider all surgical options for effective planning. The aim of this systematic review was to answer two main questions—(1) what are the risk factors for instability after rTHA? and (2) what are the best preoperative assessments and surgical options to avoid dislocation after rTHA?Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 48 publications
2
53
0
9
Order By: Relevance
“…This is in contrast to the findings of Wang who found that 22‐mm and 28‐mm femoral heads were both risk factors for dislocation in DDH patients. The small femoral head diameter has been widely accepted as a risk factor for dislocation after THA because of increased component impingement and decreased “jump distance”. In THA of Crowe type IV hips, the general consensus is that placement of acetabular component in the true acetabulum instead of a high placement can provide better hip function and longer prosthetic durability.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This is in contrast to the findings of Wang who found that 22‐mm and 28‐mm femoral heads were both risk factors for dislocation in DDH patients. The small femoral head diameter has been widely accepted as a risk factor for dislocation after THA because of increased component impingement and decreased “jump distance”. In THA of Crowe type IV hips, the general consensus is that placement of acetabular component in the true acetabulum instead of a high placement can provide better hip function and longer prosthetic durability.…”
Section: Discussionmentioning
confidence: 70%
“…Although much effort has been devoted to its prevention, the incidence of dislocation after primary THA still ranges from 1.4% to 5.0%. The risk factors for postoperative dislocation identified include patient factors (including advanced age, abductor muscle weakness, preoperative diagnosis, and so on) and surgical factors (including small femoral head size, component malposition and low soft tissue tension, and so on). Besides, the surgeon experience can influence the postoperative dislocation rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To cope with a limited ROM after a THA, prosthesis designs with larger diameter head bearings have been introduced to provide stability, a larger ROM, a smaller risk of dislocation, and to possibly prevent StL impingement. These claims have been supported in the literature [8][9][10][11][12], although concerns are still reported [13][14][15].…”
Section: Introductionmentioning
confidence: 92%
“…In primary and revision total hip arthroplasty (THA), appropriate implant size and placement is important to prevent complications such as dislocation [1] [2] [3], wear of the polyethylene liner, and loosening of the components [4][5] [6]. Lewinnek et al proposed a "safe zone" of cup alignment, and Widmer et al proposed an optimal combination of cup alignment and stem anteversion to minimize the risk of impingement [7].…”
Section: Introductionmentioning
confidence: 99%